A review on polyamine analogues and its cytotoxicity effect against selected human cancer cell lines - Abdul Ghani, Radiah; Halim, Suhana; Jamil, Masnizahani; Sahabudin, Adzly Hairee (UPM Press, 2018)
Natural polyamines such as putrescine, spermidine, and spermine are crucial for cell growth and proliferation. However, over accumulation of polyamines can lead to the worst scenario which is the progression of cancer cells. The upregulation of polyamine transport system (PTS) activity leads to an opportunity to develop more specific and effective cancer treatment. Based on this strategy, polyamines are utilized as a vector which inserted with known cytotoxic compound. Perhaps, anticancer drugs that attached to the polyamines are directly targeted the cancer cells without affecting other normal cells and the side effects of the drugs could be reduced or minimized. Therefore the aim of this paper is to review the polyamine analogues which have been synthesized and evaluated as potential anti-cancer agent in various types of cancer cell lines. It is hope that the concept of selective targeting of cancer cells via the polyamine transport system will lead to the development of novel and effective anti-cancer therapies.